Design & emotion: The Kansei engineering methodology / Anitawati Mohd Lokman - Mohd Lokman, Anitawati (Faculty of Computer and Mathematical Sciences, 2010)
Today‟s trends in product development indicated that inclusion of consumer‟s need to the technical aspect of product design will determine their success in the market. Explicit needs are clear and easy to describe. However, the implicit needs such as emotional experience are difficult to quantify. This paper introduces methods and techniques than can be used to capture consumers‟ needs in general and specifically describes the framework of Kansei Engineering to handle the implicit needs of consumers. The framework offers quick and easy understanding to the implementation of Kansei Engineering in discovering implicit consumers‟ needs and analyzes its relations to product design. The author contends that the framework is a useful guide to beginners in the industry and academia to the implementation of the technology in diversed fields including HCI, Interaction Design and the various tangible product design.